Teleconsultation for outpatient care of patients during the Covid-19 pandemic at a University Hospital in Colombia. (November 2021) - Escobar, María Fernanda; Henao, Juan Fernando; Prieto, Diana; Echavarria, María Paula; Gallego, Juan Carlos; Nasner, Daniela; Martínez-Ruíz, Diana Marcela; Velasco, Jorge Eduardo; Alarcón, Juliana
Highlights: The article describes the implementation and the result indicators evidenced by a new teleconsultation service implemented during the health emergency by COVID 19 in Colombia. A total of 56, 560 teleconsultations was realized, represented 19% of all ambulatory care, reaching the proposed target of 10%. Teleconsultation surpassed the goals of coverage indicators for the city, department, and country. The effectiveness in carrying out scheduled teleconsultations had an overall result of 91.5%, over the goal proposed of 85%. Implementing an outpatient teleconsultation model allowed the continuity of the management with comprehensive coverage nationwide from a highly complex hospital in southwestern Colombia. Abstract: Background: During the COVID 19 pandemic, direct-to-consumer telehealth (DTC) services allowed patients real-time virtual access to healthcare providers, especially those with an established relationship. In Colombia, this care modality was implemented between 2019 and 2020, under national considerations, it was implemented for outpatient care in a highly complex university hospital in Cali, Colombia. Methods:  A descriptive study with prospective information collection was used to describe the implementation of the outpatient teleconsultation care model for patients. We constructed the clinical and process indicators with which we evaluated the model. Findings: A total of 56, 560 patients from our institution were treated by virtual outpatient consultation during the first nine months of the health emergency declared by COVID 19 in Colombia. The strategy made it possible to achieve coverage more significant than 100% in Cali and the departments of Colombia. Attention by teleconsultation was 19% of the total ambulatory care. The effectiveness in carrying out scheduled teleconsultations had an overall result of 91.5%. The accessibility results demonstrated the need to strengthen connectivity and accessibility to payments and strengthen technology adoption in the institution, health personnel, and patients. Interpretation: Implementing an outpatient teleconsultation model allowed the continuity of the management with comprehensive coverage nationwide from a highly complex hospital in southwestern Colombia. The indicators' analysis should help strengthen the policies of access to telemedicine, especially with the consequences of the pandemic in low- and middle-income countries. Latin American evidence is necessary to establish the safety profile of telemedicine and the costs associated with the provision.